Fractional myocardial blood volume by ferumoxytol‐enhanced MRI: Estimation of ischemic burden. Issue 4 (16th November 2022) - Colbert, Caroline M.; Hollowed, John J.; Nguyen, Dylan N.; Duarte‐Vogel, Sandra; Dahlbom, Magnus; Hu, Peng; Nguyen, Kim‐Lien
Abstract : Purpose: To investigate model‐fitted fractional myocardial blood volume (fMBV) derived from ferumoxytol‐enhanced MRI as a measure of myocardial tissue hypoperfusion at rest. Methods: We artificially induced moderate to severe focal coronary stenosis in the left anterior descending artery of 19 swine by percutaneous delivery of a 3D‐printed coronary implant. Using the MOLLI pulse sequence, we acquired T1 maps at 3 T after multiple incremental ferumoxytol doses (0.0–4.0 mg/kg). We computed pixel‐wise fMBV using a multi‐compartmental modeling approach in 19 ischemic swine and 4 healthy swine. Results: Ischemic myocardial segments showed a mean MRI‐fMBV of 11.72 ± 3.00%, compared with 8.23 ± 2.12% in remote segments and 8.38 ± 2.23% in normal segments. Ischemic segments showed a restricted transvascular water‐exchange rate ( k i  = 15.32 ± 8.69 s −1 ) relative to remote segments ( k i  = 17.78 [11.60, 26.36] s −1 ). A mixed‐effects model found significant difference in fMBV ( p  = 0.002) and water‐exchange rate ( p  < 0.001) between ischemic and remote myocardial regions after adjusting for biological sex and slice location. Analysis of fMBV as a predictor of impaired myocardial contractility using receiver operating characteristics showed an area under the curve of 0.89 (95% confidence interval [CI] 0.80, 0.95). An MRI‐fMBV threshold of 9.60% has a specificity of 90.0% (95% CI 76.3, 97.2) and a sensitivity of 72.5% (95% CI 56.1, 83.4) for prediction of impaired myocardial contractility. Conclusions: Model‐fitted fMBV derived from ferumoxytol‐enhanced MRI can distinguish regions of ischemia from remote myocardium in a swine model of myocardial hypoperfusion.